The Prevalence of Toxoplasma gondii in Saudi Arabia (1994–2023): A Systematic Review and Meta-Analysis - Hassan N. Moafa; Abdullah H. Altemani; Ali Alaklabi; Khalid Y. Ghailan; Alkhansa Alshabi; Majid Ahmed Darraj; Hammad Ali Fadlalmola (Journal of Epidemiology and Global Health)
Abstract Toxoplasmosis is one of the most common parasites affecting humans in diverse populations caused by T. gondii. This study aims to systematically review and analyze the prevalence of T. gondii infection among various population categories in Saudi Arabia. Our search was done in five databases: PubMed, Scopus, Cochrane Library, Embase, and Web of Science to find the relevant studies from inception to November 2023. The pooled prevalence of toxoplasmosis among the total population living in Saudi Arabia was estimated using a random-effect meta-analysis approach, and Comprehensive Meta-Analysis software was utilized for this analysis. Our study included 30 case–control and retrospective studies published from 1994 to 2023 involving 20,699 patients from different regions in the Kingdom of Saudi Arabia. Various cities were included, such as Al-Ahsa, Najran, Riyadh, Arar, Mecca, al Khobar, Mushait, Tabuk, jazan, Hail City, Almadinah Almunawwarah, AL-Ahsa, and Abha; 27 reported outcomes related to IgG seroprevalence, revealing an overall toxoplasmosis prevalence of 27.5% in Saudi Arabia. Fifteen studies that measured IgM seroprevalence found an overall toxoplasmosis prevalence of 2.2%. Specifically for pregnant women, IgG seroprevalence was 28%. Among different age categories, the highest toxoplasmosis prevalence was observed in the group aged 31–45 years, reaching 32.5%, while the lowest prevalence was in the 10–20 years category at 19.3%. Regarding gravidity, the grand multi-gravida group exhibited the highest prevalence at 32.9%, with an upper limit of 47.8%. Furthermore, individuals who consumed freshwater demonstrated a higher incidence than those drinking bottled water, with respective prevalence rates of 33.5% and 29.4%. In conclusion, the prevalence of toxoplasmosis in Saudi Arabia is lower than the global average, with significant variations across different age groups, water sources, and dietary habits. Targeted educational programs and public health interventions are essential to raise awareness and reduce the risk of T. gondii infection. Future research should focus on improving study quality and exploring the broader implications of toxoplasmosis on public health in Saudi Arabia.